THE PROCESS OF FORMING AN INTERCULTURAL CONTEXT - Kamola Aripova Yusupovna (Лучшие интеллектуальные исследования, 2024)
The article notes that in the conditions of the new socio-economic realities of society, the updated goals of teaching at a language university, the requirements for mastering a foreign language as an instrument of communication are increasing. A high-quality communication process is impossible if the student is not in a state of readiness to overcome communicative difficulties, compensate for the interrupted communication process, get out of the situation of lack of language and speech resources.